Methodology to improve the accuracy of the model in photovoltaic systems - Jose Galarza (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The present research proposes a methodology to improve the estimation of the unknown parameters of the unitary diode model of the photovoltaic panel. To check the accuracy, a comparison with other methodologies known in the scientific literature is made. Through an iterative process, the best value of the series resistance and the ideality factor for different temperature and irradiance conditions are identified. The objective is to determine a simplified model that accurately estimates the power supplied by a photovoltaic installation. To check the effectiveness of the methodology, a comparison was made between the power estimated by the model and the power measurements of an experimental photovoltaic installation. The results based on statistical indicators show that the proposed methodology determines a simplified model of the unitary diode with a better capacity and accuracy with respect to the known methodologies.